2014
DOI: 10.3109/0886022x.2014.964146
|View full text |Cite
|
Sign up to set email alerts
|

Utility of cystatin C-derived equations for evaluation of residual renal function in peritoneal dialysis patients

Abstract: Cystatin C-derived equations outperform the CKD-EPI formula in approximating the RRF values. Yet, these methods still significantly overestimate the measured RRF and their routine application in clinical practice is not advised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The most recent guidelines recommend the use of cystatin C formulas for confirmation of GFR, in adults with eGFRcr of 45-59 mL min −1 1.73 m −2 without markers of kidney damage [16,48]. However, even with the association of creatinine and cystatin C, the accuracy of eGFR vs. measured GFR (mGFR) and its use for clinical decision making, especially for ESRD remain elusive [27,49,50], making the evaluation of novel filtration markers a growing area of research.…”
Section: Cystatin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent guidelines recommend the use of cystatin C formulas for confirmation of GFR, in adults with eGFRcr of 45-59 mL min −1 1.73 m −2 without markers of kidney damage [16,48]. However, even with the association of creatinine and cystatin C, the accuracy of eGFR vs. measured GFR (mGFR) and its use for clinical decision making, especially for ESRD remain elusive [27,49,50], making the evaluation of novel filtration markers a growing area of research.…”
Section: Cystatin Cmentioning
confidence: 99%
“…Use of cystatin C for estimation of residual kidney function has been studied, with equations proposed by estimated by urea/creatinine in PD patients and state that Cyst-based equations have superior sensitivity and specificity for identifying significant RKF (> 2 mL min −1 1.732 −1 ) and 30-50% higher accuracy than the Hoek formula [68]. More recently both equations were externally validated and compared to the CKD-EPI equation: it was concluded that cystatin C-derived equations outperform CKD-EPI, as well as MDRD, when estimating rGFR, although, still overestimate its value [49,50].…”
Section: New Equations To Estimate Residual Kidney Function In Dialysismentioning
confidence: 99%
“…The Chronic Kidney Disease Epidemiology Collaboration formula Cystatin C-derived equations (CDK EPI Cystatin C and CDK EPI Cystatin C-creatinine) outperform the Chronic Kidney Disease Epidemiology Collaboration formula (CDK EPI creatinine) in approximating the residual renal function values 19 .…”
Section: Renalmentioning
confidence: 99%
“…Hoek and colleagues using serum concentrations of Cystatin C showed that a simple linear equation can be used to estimate glomerular filtration rate values surpassing the accuracy of the modification of diet in renal disease creatinine formula 19 .…”
Section: Renalmentioning
confidence: 99%
See 1 more Smart Citation